The effectiveness of a computer supported intervention targeting orthographic processing and phonological recoding for children with impaired word identification - Seiler, Toni; Leitão, Suze; Blosfelds, Mara (The Speech Pathology Association of Australia Ltd., 2013)
This study investigated the effectiveness of a computer-supported intervention targeting orthographic processing and phonological recoding for word identification skills. Participants were three children (aged 7–8 years) with persistent word identification impairment. A single subject design with three phases was used, comprising a total of 31 sessions (8 baseline, 15 intervention, and a further 8 baseline) over 10 weeks. Results indicated a significant treatment effect based on measures of rate and accuracy of nonword reading measured at the start of every session. In addition, all participants made clinically significant gains in accuracy of nonword reading from pre- to post-intervention, and demonstrated mixed results with word and nonword reading efficiency.